OP0099 3d Cortical Bone Mapping of The Proximal Femur in A Large Prospective Population-Based Study Supports The Ganz Hypothesis of Hip Osteoarthritis Causation: The Ages-Reykjavik Study. (15th July 2016) - Burkov, I.S.; Treece, G.; Gee, A.; Turmezei, T.; Johannesdottir, F.; Sigurdsson, S.; Aspelund, T.; Jόnsson, H.; Gudnason, V.; Poole, K.
Abstract : Background: The mechanical aetiology hypothesis of hip osteoarthritis (OA) implicates focal mechanical wear of the joint surface from increased contact pressures, often associated with subtle abnormalities in 3D structure, such as those identified in femoro-acetabular impingement. Related to this, thickening of subchondral bone is emerging as an important disease feature in OA and may also be implicated in pathogenesis. Cortical bone mapping (CBM) is a proven technique that has been used to accurately measure structural properties of bone [1]. Objectives: CBM technique was applied to hip clinical computed tomography (CT) scans in a large prospective study of healthy older individuals to identify locations where cortical and subchondral bone in people who were destined for eventual total hip replacement (THR) to treat OA differed, on average, from healthy controls. We hypothesise that areas of thickening will coincide with lifelong habitual contact pressures, such as during walking. Methods: We undertook a prospective nested case-control study within a cohort of 3133 subjects with an average 5-year follow-up from the Age, Gene/Environment Susceptibility-Reykjavik Study (AGES-REYKJAVIK). Using a previously published method [1], CBM was applied to clinical CT scans (slice thickness 1mm) to identify the regions where cortical thickness (CTh) in the proximal femur was significantly associated to eventual THR. After quality control 25 of the samples were rejected leaving 90 THR that were performed on 75 participants (49 female, 26 male, mean±sd age 74±4.7 yrs) at a mean±sd of 35.6±24.6 months after baseline CT scan, matched to 185 controls (117 female, 68 male, mean±sd age of 74±4.7 matched for calendar year of recruitment, sex and age). CTh measurements were spatially aligned onto an average femur surface and statistical parametric mapping used to analyse the results presented as percentage difference between cases and controls. The model allowed for size, the first five non-rigid shape modes, group (case*control), age, sex, weight and height. Results: We found highly focal regions of up to 70% greater CTh in the proximal femur, especially at the femoral head, among men and women who had a subsequent THR when compared to controls. Cortical and subchondral bone plate thickening in OA coincides with simulated peak contact pressure areas of the human hip [2], but is absent in less loaded regions of the hip. Conclusions: CBM and SPM show a pattern of femoral cortical bone and subchondral bone plate thickening in a large population destined for THR compared with controls in a novel 3D analysis that does not rely on subjective assessment of CT images. Such thickening patterns support the mechanical aetiology (Ganz) hypothesis of hip OA causation. References: Treece, G.M. and A.H. Gee, Independent measurement of femoral cortical thickness and cortical bone density using clinical CT. Med Image Anal, 2015. 20(1): p.249–64. Henak, C.R., et al., Specimen-specific predictions of contact stress under physiological loading in the human hip:validation and sensitivity studies. Biomechanics and modeling in mechanobiology, 2014. 13(2): p.387–400. Disclosure of Interest: None declared